STUDY ON ORGANIZING PRACTICES OF NON-PRINT MATERIALS FOR ACCESS IN SPECIAL LIBRARIES OF SRI LANKA - WPAYARATNE, I.D.A.L. (DEGREE OF MASTER IN LIBRARY AND INFORMATION SCIENCE, 2003)
Non-print materials were able to find a place for themselves in library shelves around the world since the World War II. Rapid decrease of price of certain non-print materials during last two decades brought a golden era to the non-print materials as information sources. It is true that non-print materials raised new issues to the libraries. But it is the librarian's professional responsibility to provide information in spite of the formats they are been stored. Therefore, many professionals of library and information field, have done investigations, surveys, experiments and researches to identify the difficulties, failures, gaps as well as opportunities to develop the collections; enhance access potential and extend services of non-print materials. This study tries to identify the current situation (availability and organization level) of non-print materials as library items in special libraries of Sri Lanka and to identify the type of progress we can anticipate in near future. The findings of this research revealed that we were not in a very happy position in both aspects. Over 75% of special libraries did not have non-print collections of at least 100 items. Variety of types of non-print materials was also very limited. (There were only six types - audiocassettes, videocassettes, motion pictures, slides, microforms and CD ROMs - that included at least 10% of surveyed libraries.) The other feature that was visible was the dominancy of one or two types in most of the collections. (There wasn't any library, which included all six identified types and only around 12% of libraries included five types.) Audiocassettes (47%), videocassettes (44%) and CD-ROMs (37%) showed the highest majority in distribution rate over the other types. Therefore it was clear that the libraries providing non-print services in Sri Lanka was limited and they also depended on one or two familiar types rather than going for variations or experiments. Various aspects of classification and cataloguing have been investigated in this study. Data was organized to measure the level of organization of non-print materials compared to printed materials and impact of number of items in the collection on the application of the organizational techniques. It was very clear that application of standard cataloguing codes and classification schemes for non-print materials was always below that of printed materials. Usage of standard systems to non-print materials was also decreasing with increasing number of items in the collection while usage of in-house schemes increasing. The computerization of catalogues illustrated somewhat satisfactory progress but it decreased with increased number of items so as the availability of integrated catalogues. However the integrated shelving was unfamiliar to almost all surveyed libraries although they were providing open access and lending facilities to some selected types of non-print materials. We cannot expect many changes in the near future, as there was lack of future plans to do so. Librarians' attitudes and knowledge were also not developed enough for such change. However they believed that non-print materials were not too expensive for libraries to afford and higher percentage of them were willing to apply standard systems for cataloguing and classification; and like to provide open access and lending facilities; for non-print materials, more than they currently practice. Lack of opportunities for librarians to specialized in the non-print field; update and share the knowledge and the experience with local and foreign experts were seem to be obstacles more than financial restrictions.